Factors Associated with Successful Trial of Labor after Cesarean Section: A Retrospective Cohort Study. (3rd June 2018) - Thapsamuthdechakorn, Aram; Sekararithi, Ratanaporn; Tongsong, Theera
Abstract : Objective . To determine the effectiveness of trial of labor after cesarean section (TOLAC) and the factors associated with a successful TOLAC. Materials and Methods . A retrospective cohort study was conducted on consecutive singleton pregnancies with a previous single low-transverse cesarean section planned for TOLAC at a tertiary teaching hospital. The potential risk factors of a successful TOLAC were compared with those associated with a failed TOLAC. A simple audit system used in the first two years was also taken into account in the analysis as a potential factor for success. Results . During the study period, 2, 493 women were eligible for TOLAC and 704 of them were scheduled for TOLAC, but finally 592 underwent TOLAC. Among them, 355 (60%) had a successful vaginal birth and 237 (40%) had a failed TOLAC. The independent factors associated with the success rate included the audit system, prior vaginal birth, low maternal BMI, and lower birth weight or gestational age, whereas induction of labor and recurring indications in previous pregnancy significantly increased the risk of having a failed TOLAC. Strikingly, the strongest predictor of a successful TOLAC was the audit system with OR of 6.4 (95%CI: 3.9-10.44), followed by a history of vaginal birth in previous pregnancies (OR: 3.2; 95%CI: 1.87-5.36). Conclusion . The simple audit system had the greatest impact on the success rate of TOLAC, instead of the less powerful obstetrical factors as reported in previous reports. The audit system is the only potential factor that could be strengthened to improve the success rate.